Karakteristik Jaringan Ulama Nusantara menurut Pemikiran Azyumardi Azra - Nurdinah Muhammad (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2012)
Study on transmission and spread of purifying ideas in 17th and 18th centuries focuses on the role of ulama, that Azyurmadi specifically stress on the importance of Tasawuf and rationality. He opines the tasawuf is one of the other side of Islam. Shariah and Fiqh are on one side, while the second side is tasawuf. Islamization would be perfect if both sides are combined together; the fiqh and the tasawuf. If mankind only stresses on one of them, let‟s say fiqh only, the plurality of human life will be brought to the legalistic tendencies. Therefor. the mystical understanding on religious teaching is required. That is why Azyumardi highly appreciates zikir and alike that make mankind become closer to Allah.